2020
DOI: 10.1111/bjd.19150
|View full text |Cite
|
Sign up to set email alerts
|

High somatostatin receptor expression and efficacy of somatostatin analogues in patients with metastatic Merkel cell carcinoma*

Abstract: Summary Background Merkel cell carcinoma (MCC) is an aggressive, high‐grade, cutaneous neuroendocrine tumour (NET). Agents blocking programmed death 1/programmed death ligand 1 have efficacy in metastatic MCC (mMCC), but half of patients do not derive durable benefit. Somatostatin analogues (SSAs) are commonly used to treat low‐ and moderate‐grade NETs that express somatostatin receptors (SSTRs). Objectives To assess SSTR expression and the efficacy of SSAs in mMCC, a high‐grade NET. Methods In this retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
1
34
0
1
Order By: Relevance
“…A previous study by Akaike et al . examining the use of somatostatin analogues to treat metastatic MCC with high somatostatin receptor expression found that these receptor analogues led to clinically significant disease control 8 . Taken together, our results demonstrate that evaluating MCC tumour‐targeted therapies must continue.…”
Section: Figurementioning
confidence: 62%
“…A previous study by Akaike et al . examining the use of somatostatin analogues to treat metastatic MCC with high somatostatin receptor expression found that these receptor analogues led to clinically significant disease control 8 . Taken together, our results demonstrate that evaluating MCC tumour‐targeted therapies must continue.…”
Section: Figurementioning
confidence: 62%
“…In the largest cohort study, 85% of MCC patients ( n = 39) had at least some degree of 111 In-pentetreotide uptake in SSTR scintigraphy, with the majority (75%) showing low to medium tracer uptake. However, the SSTR expression status, assessed by scintigraphy, did not significantly correlate with clinical outcomes of SSTR-targeted therapy [ 73 ].…”
Section: Non- 18 F-fdg Pet Tracers In MCCmentioning
confidence: 99%
“…Their use in clinical trials is increasingly recognized by regulatory authorities, clinicians and patients because they help to indicate whether the impact of an intervention is comprehensively assessed. 4 In this issue of the BJD, Bhat et al 5 use qualitative research to assess the impact of CTCL on patients' daily lives and to identify the most meaningful aspects in assessing QoL in CTCL. This is achieved by evaluating existing QoL instruments (generic, skin specific and disease specific).…”
mentioning
confidence: 99%
“…In this issue of the BJD, Akaike et al 4 report the Seattle experience with targeting somatostatin receptors (SSTRs), transmembrane proteins frequently expressed by neuroendocrine cancers. SSTR expression was assessable by either imaging or immunohistochemistry in 40 patients with MCC, of whom 19 were evaluable for their response to a somatostatin analogue (octreotide long-acting release).…”
mentioning
confidence: 99%
See 1 more Smart Citation